1998
DOI: 10.2115/fiber.54.2_77
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Recognition of N-.ALPHA.-Acetyltryptophans with Molecularly Imprinted Polymeric Membranes Containing DVNE Derivatives.

Abstract: Molecularly imprinted polymeric membranes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…1, and those reported previously [27][28][29][30][31][32][33] , it can be said that the chiral recognition site toward L-isomer was formed by the presence of the print molecule Ac-L-Trp during the membrane preparation process. 1, Fig.…”
Section: Adsorption Isotherms Of Ac-d-trp and Ac-l-trpsupporting
confidence: 55%
See 2 more Smart Citations
“…1, and those reported previously [27][28][29][30][31][32][33] , it can be said that the chiral recognition site toward L-isomer was formed by the presence of the print molecule Ac-L-Trp during the membrane preparation process. 1, Fig.…”
Section: Adsorption Isotherms Of Ac-d-trp and Ac-l-trpsupporting
confidence: 55%
“…The adsorbed amounts are given not only in absolute but also in relative values which are based on the EFF derivative for convenience in the following discussion. Therefore, the present membrane having a tripeptide derivative as a chiral recognition site also gave adsorption selectivity like those with a tetrapeptide derivative [27][28][29][30][31][32][33] . 1, the results summarized in Tab.…”
Section: Adsorption Selectivity Of Racemic Amino Acidsmentioning
confidence: 76%
See 1 more Smart Citation
“…Some membranes prepared in the present study, of which constituting amino acid residue numbers of three to six, showed adsorption selectivity toward the L-isomer, like the molecularly imprinted polymers from tetrapeptide derivatives. 19 From the previously reported data, 8,[20][21][22] it is known that the polymer prepared in the absence of a print molecule does not show a chiral recognition ability. The molecularly imprinted polymers from D-resin, DI-resin, DIDEDID-resin, and DIDEDIDE-resin hardly showed adsorption selectivity.…”
Section: Results and Discussion Adsorption Selectivity Of Racemic Ac-mentioning
confidence: 99%
“…It is necessary to introduce physical stereoselectivity into synthetic membranes so that they can separate mixtures of optically active compounds. The authors adopted oligopeptides, 23,25,27,30,33,34,36 a derivative of natural polymer, 31 and nonchiral synthetic polymer 35 as candidate materials to form chiral recognition sites; these materials were converted into chiral recognition sites toward amino acids or amino acid derivatives by applying an alternative molecular imprinting technique. That is, molecular memory of the print molecule, which is separated or recognized, is introduced in the membrane simultaneously while the polymeric membrane is prepared from its polymer solution (i.e., membrane preparation with simultaneous molecular imprinting).…”
Section: Introductionmentioning
confidence: 99%